Usability Testing Pada Software Line Messenger - Wijaya, Oki; Nathanael, Sievin; Wicaksono, Soetam (LPPM Universitas Sains dan Teknologi Komputer, 2022)
This study aims to perform Usability Testing on software or freeware applications, namely LINE Messenger. Usability Testing itself is a method of evaluating the usability of software (Software) which aims to increase the usability of an application / product by analyzing, identifying problems, measure efficiency, measure convenience and determine user satisfaction. Usability testing for the LINE Messenger application is carried out to determine the level of ease of use of the Line application, such as ease of understanding features, memory location of features, and also assessing the User Interface (UI). to the application, preparing test scenarios, looking for respondents or testing subjects, making questionnaires with the System Usability Scale (SUS) standard, and conducting usability analysis on the results of respondents and questionnaires. Then the final output is in the form of reports and conclusions regarding the results of the analysis. LINE Messenger itself is a popular social media application, an application that has many features such as LINE Today, Share screen and also has a LINE Shop. LINE itself is an easy-to-use application, with the results of the questionnaire showing positive Usability Testing results for LINE Messenger.